This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can you please provide me an intuitive proof of the reflection formula?
Log in to reply
I = ∫ a b f ( a + b − x ) d x = − ∫ b a f ( u ) d u = ∫ a b f ( u ) d u = ∫ a b f ( x ) d x Let u = a + b − x ⟹ d u = − d x when x = a ⟹ u = b and x = b ⟹ u = a Replace u with x
Problem Loading...
Note Loading...
Set Loading...
I = ∫ − 1 1 ( 2 0 2 0 x + 1 ) 6 x 2 + 6 d x = 2 1 ∫ − 1 1 ( ( 2 0 2 0 x + 1 ) 6 x 2 + 6 + ( 2 0 2 0 − x + 1 ) 6 x 2 + 6 ) d x = 2 1 ∫ − 1 1 ( ( 2 0 2 0 x + 1 ) 6 x 2 + 6 + ( 1 + 2 0 2 0 − x ) ( 6 x 2 + 6 ) ( 2 0 2 0 x ) ) d x = ∫ − 1 1 ( 3 x 2 + 3 ) d x = x 3 + 3 x ∣ ∣ ∣ ∣ − 1 1 = 8 By reflection ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x